An examination of the relationship between personality and aggression using the general aggression and five factor models. Issue 2 (5th November 2013) - Hosie, Julia; Gilbert, Flora; Simpson, Katrina; Daffern, Michael
<x xml:space="preserve">Abstract</x> This study examined the relationships between personality and aggression using the general aggression (GAM, Anderson and Bushman [2002] Annual Review of Psychology, 53, 27–51) and five factor models (FFMs) (Costa and McCrae [1992] Revised NEO Personality Inventory (NEO‐PI‐R) and NEO Five‐Factor Inventory (NEO‐FFI) professional manual. Odessa, FL: Psychological Assessment Resources). Specifically, it examined Ferguson and Dyck's (Ferguson and Dyck [2012] Aggression and Violent Behavior, 17, 220–228) criticisms that the GAM has questionable validity in clinical populations and disproportionately focuses on aggression‐related knowledge structures to the detriment of other inputs, specifically personality variables. Fifty‐five male offenders attending a community forensic mental health service for pre‐sentence psychiatric and/or psychological evaluation were assessed for aggressive script rehearsal, aggression‐supportive normative beliefs, FFM personality traits, trait anger and past aggressive behavior. With regard to relationships between five factor variables and aggression, results suggested that only agreeableness and conscientiousness were related to aggression. However, these relationships were: (1) weak in comparison with those between script rehearsal, normative beliefs and trait anger with aggression and (2) were not significant predictors in hierarchical regression analysis when all of the significant univariate predictors, including GAM‐specified variables were regressed onto life history of aggression; normative beliefs supporting aggression, aggressive script rehearsal, and trait anger were significantly related to aggression in this regression analysis. These results provide further support for the application of the GAM to aggressive populations. Aggr. Behav. 40:189–196, 2014. © 2013 Wiley Periodicals, Inc.